Search for outliers by fuzzy logic systems – general concepts - Kacprowicz, Marcin (Wydawnictwo Politechniki Łódzkiej, 2021)
This article presents both a review of the literature and research proposals on the use of artificial integration, in particular fuzzy logic and fuzzy logic systems to search for and find exceptions outlier.
Keywords: intelligence; search for outliers; finding outliers; fuzzy logic; inteligencja; wyszukiwanie wartości odstających; znajdowanie wartości odstających; logika rozmyta